Mitigação das alterações climáticas em batata-doce por meio de filme de partículas de cálcio - Ferreira, Jacqueline Alves Borges (2022)
Given the current global climate change scenario, changes in plants' adaptive behavior are expected, with variations in physiology, gene expression, and leaf anatomy. It is essential to define which genes will be responsive and which are the variations in tissue structures and the variations in physiological processes that may occur to understand and evaluate these changes. This work was carried out considering the lack of information in Literature on such variations in sweet potato plants photoprotected by particle films in situations of water restriction. It was targeted to apply photoprotective treatment with particle film (CaO 10% w/v) on the leaf surface of sweet potato plants and to evaluate variations in gene expression, ecophysiological parameters, gas exchange, and leaf anatomy. For that, it prospected in a theoretical study that the genes are involved in different adaptive mechanisms in plants. Potential genes were identified, and correlations and co-expression were sought using GeneMANIA and Cytoscape software. For field trials, the treatments were implemented between November 2018 and March 2019 at the Experimental Station Rural Campus of the Applied Agrarian Sciences Center of the Federal University of Sergipe (UFS). Ecophysiological parameters based on gas exchange estimates, the difference between air and leaf temperature, Falker indices, the fluorescence of chlorophyll a, gene expression (cdc2a), and leaf anatomy were collected at different stages of plant development, with and without water restriction. Particle film photoprotection minimized the harmful effects caused by abiotic stresses, contributing to an increase in photosynthetic rate (A) and a more significant difference between air and leaf temperature as a positive adaptive adjustment, even under conditions of water restriction. There was a reduction in the fluorescence of chlorophyll a estimates, related to the maximum cross-section (CSm) with particle film and a significant increase in the effective quantum yield (ɸPSII), electron transport rate (ETR), maximum quantum yield (Fv/Fm), and photochemical quenching (qP). In this plant homeostasis mechanism, which was identified with the photoprotective use of particle film, there was a reduction in the expression of the cdc2a gene related to light intensity stress, and anatomical variations were identified in the diameter of the leaf midrib (DNC), which is an essential variable for assessing the hydraulic conductance of plants and also crucial to predicting water transport efficiency. In parallel with water restriction, each of these changes is part of a set of plant responses in favor of tolerance or adaptation in stress situations. Thus, because of the abiotic conditions imposed on the plants, photoprotection with particle film is a management technique for sweet potato crops.